PENGARUH MODEL PEMBELAJARAN MAKE A MATCH DAN MOTIVASI TERHADAP PRESTASI BELAJAR IPS SISWA SMPN 1 KARANGPLOSO - Yuliananingsih Yuliananingsih (Center of Language and Cultural Studies, 2017)
This experimental research examines: (1) a significant influence of “make a match” model to attainment in IPS course of the students of SMPN 1 Karangploso; (2) a significant influence of motivation model on the achievement IPS course; and (3) a significant influence between the type of “make a match” model and motivation model on the accomplishment of IPS course. The sample of this research was the 98 students of IX grade at SMPN 1 Karangploso Malang. The research revealed that: (1) “the make a match” learning model significantly influences learning achievement of IPS course of the students of SMPN 1 Karangploso; (2) motivation model significantly affects learning achievement of IPS, and (3) “the make a match” learning model and motivation model significantly influence achievement of IPS course.